Komposisi Kimia dan Ketahanan Rotan Asal Sulawesi Tenggara terhadap Serangan Rayap Tanah (Chemical Composition and Durability of Rattan Originated Southeast Sulawesi Against Subterranean Termites) - Esti R Satiti; Nur A Saputra; Titi Kalima (Masyarakat Peneliti Kayu Indonesia, 2017)
Rattan is one of the most popular non-timber forest products. Globally, there are 850 rattan species grown in the world, and 312 species of them were naturally grown in Indonesia and 35 species found in Sulawesi Island. This paper studies the chemical composition of 8 types of rattan from Southeast Sulawesi and its durability against subterranean termite (Coptotermes curvignathus Holmgren). The parameters tested include cellulose and lignin. Cellulose was determined by Norman and Jenkins method, while lignin was determined based on the Indonesian National Standard (SNI 14-0492-1989). Rattan natural durability is tested against Indonesian National Standard (SNI 01-7207-2014). Result shows that the highest cellulose content was found in umili rattan (Calamus macrosphaerion Becc.) which is about 55%, while the lowest cellulose content was found in kuku hitam rattan (Calamus lorelinduensis Becc.) which is about 47.25%. The highest lignin content was recorded at cabang rattan (Korthalsia celebica Becc., 30.78%), while the lowest lignin was recorded at umili rattan (Calamus macrosphaerion Becc., 21.18%). Two rattan were classified into class I, and three rattan were classified into class II, two rattan species into class III and one species is classified into class V.Keywords: chemical composition, durability, rattan, subterranean termites